2009
DOI: 10.1001/archoto.2009.150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Single-Trial Results on Clinical Practice

Abstract: isrctn.org Identifier: ISRCTN04973569.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This results suggest that any active intervention to implement evidence is more effective than passive dissemination of evidence based interventions [10,11]. Other systematic reviews on implementation strategies in general, however, report on ineffective strategies or strategies with an uncertain or variable effectiveness [24,25].…”
Section: Some Potential Limitations Are Worth Discussingmentioning
confidence: 96%
See 2 more Smart Citations
“…This results suggest that any active intervention to implement evidence is more effective than passive dissemination of evidence based interventions [10,11]. Other systematic reviews on implementation strategies in general, however, report on ineffective strategies or strategies with an uncertain or variable effectiveness [24,25].…”
Section: Some Potential Limitations Are Worth Discussingmentioning
confidence: 96%
“…Passive dissemination of trial results and meta-analyses, may therefore not reach these professionals [9], nor affect how they manage their patients [10,11] In general, clinical practice guidelines are issued to this matter. Alternative strategies comprise educational materials, education sessions, audits and feedbacks, reminders and computerized decision support systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite remarkable because impaired dissemination of practice guidelines and clinical research into daily practice has been reported repeatedly. 17,[19][20][21][26][27][28] Since the patients with OSAHS in the scenarios were well treated according to the guidelines, the implementation of the current OSAHS guidelines in clinical practice can be considered successful. The authors of the Dutch OSAHS guideline 4 reported several actions to promote awareness and implementation of the guidelines: they were actively distributed among all relevant associations and hospitals; an abstract of the guidelines was published in the Dutch Journal of Medicine and several related clinical journals; the content of the guidelines was published on the Dutch Institute for Health Care Improvement (Centraal Begeleidings Orgaan) (CBO) Web site, 4 and the guidelines were discussed at several scientific conventions and audits of the related societies.…”
Section: Commentmentioning
confidence: 99%
“…Over 70% of otolaryngologists who responded to our survey had read the guideline, which is encouraging as the document had only been released slightly over 1 year prior to commencement of this study. This is notable because impaired dissemination of CPGs and clinical research into daily practice has been reported in a number of studies . Another encouraging finding is the high rate of adherence to the 2 strong guideline recommendations.…”
Section: Discussionmentioning
confidence: 84%